2018
DOI: 10.1139/cjce-2017-0432
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and control of variable approach lanes on an arterial road: a case study of Dalian

Abstract: Unbalanced directional traffic, which often exists at intersection approaches, is an important factor to induce traffic congestion on urban streets. Considering the settings of variable approach lanes, the presence of left-turn bays, and a variety of vehicle categories on an arterial road, an optimization model that minimizes the total delay is formulated and a control method that coordinates a variable sign and the corresponding signal group is put forward. To design the signal control scenarios with time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Regarding equation (18), the number of vehicles in a platoon has an important influence on the optimized value of the offset between paired intersections. When the intersection spacing is certain, such an offset is very sensitive to the number of vehicles in a platoon [32]. If Model CS is used for future design, the number of vehicles in a platoon can be set to 20 pcu, as shown earlier.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Regarding equation (18), the number of vehicles in a platoon has an important influence on the optimized value of the offset between paired intersections. When the intersection spacing is certain, such an offset is very sensitive to the number of vehicles in a platoon [32]. If Model CS is used for future design, the number of vehicles in a platoon can be set to 20 pcu, as shown earlier.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…The time interval adopted for short-term traffic flow prediction is usually less than half an hour. Also, the peak 15-minute flow rate is usually adopted for signal timings [6]. Thus, a 15-minute time interval 7 is used to aggregate the selected data.…”
Section: Case Studiesmentioning
confidence: 99%
“…Furthermore, Ma et al [5] indicated that the change rules of traffic flow data during different weekdays are various and those during different weekends are also various. For urban traffic flow, the fluctuations of data during different periods in a day or for different vehicle types are also various [6]. Thus, the period division and vehicle type are considered when predicting traffic flow in this research.…”
Section: Introductionmentioning
confidence: 99%
“…For isolated intersections with obvious tidal congestion, it is difficult to solve the congestion problem simply by optimizing traffic signal control. Yao et al [1] pointed out this problem, and solved it considering time-dependent unbalanced directional traffic flow. This problem has been studied by many researchers using the variable lane setting approach effectively.…”
Section: Introductionmentioning
confidence: 99%